1999
DOI: 10.1034/j.1399-0012.1999.t01-2-130107.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of support for organ donation among three ethnic groups

Abstract: Telephone interviews about organ donation were conducted with 4880 white respondents, 634 African-American respondents and 566 Hispanic respondents. Forty-three percent (42.9%) of whites, 31.2% of Hispanics and 22.6% of African-Americans reported that they were willing to donate their organs after their death (p < 0.001). Logistic regression analysis revealed three significant correlates of willingness to donate across all ethnic groups: having had a family discussion about end-of-life issues; the belief that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 13 publications
6
105
0
Order By: Relevance
“…Drawing from existing measures in the research literature, we created a 24-item scale that captured attitudes and beliefs about donation and transplantation [6,30,43,44]. This scale included items that measured support for donation, willingness to donate to people of other racial/ethnic groups, religious objections to donation, concerns that donation might hasten death, trust in the donation and transplantation system, and perceptions of equality in the transplant system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing from existing measures in the research literature, we created a 24-item scale that captured attitudes and beliefs about donation and transplantation [6,30,43,44]. This scale included items that measured support for donation, willingness to donate to people of other racial/ethnic groups, religious objections to donation, concerns that donation might hasten death, trust in the donation and transplantation system, and perceptions of equality in the transplant system.…”
Section: Methodsmentioning
confidence: 99%
“…Among African Americans in particular, studies using a composite measure of knowledge demonstrate that overall knowledge about organ donation is an important predictor of willingness to donate [6,26,[38][39][40][41]. However, less research has explored how different types of knowledge relate to donation intentions among African Americans.…”
Section: Lack Of Knowledge As a Barrier To Donation Among African Amementioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Recently, concentrated efforts have been undertaken, both in the media and at the level of local organ procurement organizations, to encourage organ donation, not only in the black population, but on a wider national scale. Despite these efforts to improve organ procurement, the slight increase in donation has not kept pace with the number of people waiting for a lifesaving organ transplant.…”
mentioning
confidence: 99%
“…In addition to lack of awareness and lack of knowledge Yancey et al, 1997), religion (Reitz & Callender, 1993;Wittig, 2001;Yancey, et al, 1997) preference for directed donation (Arnason, 1991;Hall, et al, 1991;Lange, 1992;Reitz & Callender, 1993), medical mistrust (e.g. McNamara, et al, 1999;Plawecki, et al, 1988;Reitz & Callender, 1993;Siminoff & Arnold, 1999;Siminoff & Chillag, 1999;Spigner, et al, 1999;Yancey, et al, 1997;Yuen, et al, 1998), and a desire to maintain bodily integrity (McNamara, et al 1999;Rubens & Oleckno, 1998;Spigner, et al, 1999) are the major reasons cited by researchers for African Americans' unwillingness to donate organs. Morgan and Cannon (2003) conducted a study of 300 African American adults in New Jersey, which demonstrated that there are key barriers that require particular attention when targeting African Americans with organ donation messages.…”
Section: African Americans and Organ Donor Registries In North Carolinamentioning
confidence: 99%